Conformal invariance of the pure spinor superstring in a curved background - Chandía, Osvaldo; Vallilo, Brenno Carlini [UNESP] (Springer Nature, 2004)
It is shown that the pure spinor formulation of the heterotic superstring in a generic gravitational and super Yang-Mills background has vanishing one-loop beta functions. © SISSA/ISAS 2004.
Keywords: Conformal Field Models in String Theory; Superstrings and Heterotic Strings